Rumah Kedai Tok Jamal, Lot 377 & 378, Jalan Nara, Pasir Puteh, Kelantan / [mikrofilem] - Nurul Syala Abdul Latip; Juliana Idris; Khoo, Yee Tick; Lee, Shiuan Ann; Mahadthir Suhaimi (Skudai : Universiti Teknologi Malaysia, 1996)
Kajian Lukisan Terukur (Jabatan Senibina)) - Universiti Teknologi Malaysia, 1996